INVESTIGATION OF ROLE OF CASR GENE POLYMORPHISM IN THE PATHOGENESIS OF PATIENTS WITH CHRONIC RENAL FAILURE - Kargun, Kursat (Parlar Scientific Publications (P S P), 2018)
Chronic renal failure (CRF) is an independent risk factor for all cause-mortality in general population. Renal failure has become one of the major challenges, resulting in a serious public health issue and economical burden. Kidneys filter fluids and waste materials and can reabsorb or secrete nutritional elements. Calcium-sensing receptor (CaSR) protein is located in renal cells. Increased calcium binding to CaSR prevents reabsorption of calcium from filtered fluids. The CaSR is a typical G protein-coupled receptor. Single nucleotide polymorphism (SNP) of Rs17251221 is found in an intron of CaSR gene. In this study, we investigated effects on patients with renal failure by analyzing relationship between prognosis of patients with chronic renal failure and Rs17251221 genotype. This study compared data from 138 CRF cases with 136 healthy controls. The Rs17251221 polymorphism was evaluated in DNA samples extracted from patients and controls by using real-time polymerase chain reaction (PCR). There were significant differences in body mass index (BMI), glomerular filtration rate (GFR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and urea and creatinine values (p<0.05) while there was no significant difference in calcium and sodium parameters between CRF patients and controls (p>0.05). The Rs17251221 AA genotype was detected in 112 patients with CRF (81.6%) and 120 controls (88.24%) while Rsl 7251221 AG genotype as detected in 26 patients with CRF (18.84%) and 16 controls (11.76%) (p=0.3394). No Rs17251221 GG genotype was observed in either CRF patients or controls. No significant correlation was detected between CRF development and CaSR polymorphism (p=0.6851). In this study, Rs17251221 variant had no significant relationship with CaSR gene polymorphism while significant correlations were detected between Rs17251221 variant and GFR, SBP, DBP, urea, creatinine, sodium and calcium.
Keywords: Chronic renal failure; CaSR; Rs17251221; gene polymorphism